Investigation of the influence of the tumbling angle on a tumbling self-piercing riveting process - Wituschek, Simon; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2022)
To achieve the climate objectives, various measures are taken to increase the efficiency of raw materials and energies used. A sector with a large proportion of the global consumption of resources is the mobility sector. To increase the efficiency in this field, large efforts are made to reduce the weight of moving masses. One approach is the use of multi-material systems, which utilises different materials and their specific properties depending on the local requirements. Multi-material systems consist often of materials which differ in strength and density, for example, high-strength steels, aluminium alloys or polymers. Additionally, such a system can utilise different geometries of the components to be joined, characterised for example by varying sheet thicknesses. A central challenge of producing these systems is the joining of the individual components. This requires robust joining processes capable of covering the entire spectrum of possible variants and is feasible for different physical properties of the materials. Since conventional joining processes are rather rigid and have difficulty reacting to changing process and disturbance variables, new joining processes are necessary. With the objective of being able to react versatile to varying parameters, a process combination consisting of a semi-tubular self-piercing riveting process and orbital forming process with adjustable tumbling kinematic is introduced. Due to the process combination of tumbling and self-piercing riveting, mutual influences of the two process components are analysed in regard to material flow and process forces. Further, the investigations show the influence of a varying tumbling angle on the joining process itself and how the characteristic properties undercut, rivet head end position and residual sheet thickness of the joint are affected. The material used for the joining partners is an aluminium alloy EN AW-6014 typical for multi-material systems in the automotive industry and the rivets are from type Rivset C produced by the Böllhoff company.<br
Keywords: Self-piercing riveting; joining; orbital forming